Satisfaction of service quality Islamic Banking among UiTM Puncak Alam students / Che Nur Hasyimah Che Hasanusi - Che Hasanusi, Che Nur Hasyimah (2019)
The purpose of this study was to examine student satisfaction on service quality Islamic banking in Malaysia. These respondents were students of UiTM Puncak Alam. The questionnaire was distributed to 59 students. Data was analyzed using SPSS software version 18. The data was tested by using quantitative method to anlysis the question of study and achieve the objective of this study. The objective of the study is to analyze the aspects of service quality that may affect customer satisfaction.and to identify the level of customer satisfaction with the aspect of service quality Islamic banking. The result of the study was shows that students agreed that service quality of Islamic banking in Malaysia is good and they satisfied with service quality of Islamic banking in Malaysia. Through the analysis, the results showed that there is a positive relationship between the level of student satisfaction with dimensions of compliance, assurance, reliability, tangible, and empathy.